Fecal microbiota transplantation inhibited neuroinflammation of traumatic brain injury in mice via regulating the gut–brain axis - Hu, Xuezhen; Jin, Hangqi; Yuan, Shushu; Ye, Tao; Chen, Zhibo; Kong, Yu; Liu, Jiaming; Xu, Kaihong; Sun, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: Recent studies have highlighted the vital role of gut microbiota in traumatic brain injury (TBI). Fecal microbiota transplantation (FMT) is an effective means of regulating microbiota-gut-brain axis, while the beneficial effect and potential mechanisms of FMT against TBI remain unclear. Here, we elucidated the antineuroinflammatory effect and possible mechanism of FMT against TBI in mice via regulating microbiota-gut-brain axis. Methods: The TBI mouse model was established by heavy object falling impact, and then was treated with FMT. The neurological deficits, neuropathological change, synaptic damage, microglia activation, and neuroinflammatory cytokines production were assessed, as well as the intestinal pathological change and gut microbiota composition were also evaluated. Moreover, the population of Treg cell in the spleen were measured. Results: Our results showed that FMT treatment significantly alleviated neurological deficits and neuropathological changes, and improved synaptic damage by increasing levels of the synaptic plasticity related protein such as postsynaptic density protein 95 (PSD-95) and synapsin I in the TBI mice. Moreover, FMT could inhibit the activation of microglia, reduce the production of inflammatory cytokines TNF-α, alleviating the inflammatory response of TBI mice. Meanwhile, FMT treatment could attenuate intestinal histopathology changes and the gut microbiota dysbiosis, and increase Treg cell population in the TBI mice. Conclusions: These findings elucidated that FMT treatment effectively suppressed the TBI-induced neuroinflammation via regulating gut microbiota-gut-brain axis, and its mechanism was involved in the regulation of peripheral immune cells, which implied a novel strategy against TBI.